Blunt trauma of the scrotum and testicle: algorithm of choice of treatment tactics - S. K. Yarovoy; R. A. Khromov (Исследования и практика в медицине, 2018)
Purpose of the study. The aim of this study is to improve the quality of emergency urological care for patients with scrotal and testicular trauma.Patients and methods. The study is a comparison of the results of prospective (according to the algorithm) and retrospective fragments, including a total of 459 patients (414 retrospectively, 45 prospectively). Patients received inpatient urological care for traumatic damage to the scrotum and testicle in D. Pletnyov City Clinical Hospital Department of Health of Moscow, N. Lopatkin Scientific Research Institute of Urology and Interventional Radiology — Branch of the National Medical Radiology Research Centre of the Ministry of Health of the Russian Federation for the period 2008-2018.Results. The article analyzes the clinical effectiveness of the developed algorithm for the choice of therapeutic tactics in different variants of scrotal and testicular injuries. The key differences between the proposed algorithm and the generally accepted tactics are the extension of indications for emergency testicular revision (to operate with hematocele of any volume) and the same type of antibacterial prevention/therapy of infectious posttraumatic orchitis, regardless of the nature of the injury.Conclusion. When using the algorithm, the following clinical advantages were noted: reducing the likelihood of acute post-traumatic orchitis 2.4 times (p = 0,0271); reduced likelihood of postoperative infectious-inflammatory complications is reduced 2.0 times; reducing the likelihood of orchiectomy or hardening of the testicle 1.4 times.